2020
DOI: 10.34141/ljcs2640133
|View full text |Cite
|
Sign up to set email alerts
|

Current Pharmacological Therapy against COVID-19: A Latin American Perspective

Abstract: Introduction. SARS-CoV-2 infection is a public health emergency and several treatments against COVID-19 are in place while investigated simultaneously. Objective. To update on current pharmacological therapies against COVID-19, and its implications in Latin American countries. Material and Methods. Publications on PubMed and in open access journals regarding pharmacological interventions against SARS-CoV-2 infection were reviewed, followed by analysis of the protocols already in place in Latin American countri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Due to the lack of control groups, our findings should be interpreted as preliminary and by no means as evidence to support any treatment scheme, which is still a topic largely debated with no consensus [21]. Lopinavir and Ritonavir treatment was exclusively used in ICU patients, a case control study published on March 18 th suggested a lack of effect in death reduction [63,64], however ICU attendant from this hospital decided to continue with the antiviral treatment scheme due to the lack of literature consensus and an apparent clinical improvement still on quantification.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the lack of control groups, our findings should be interpreted as preliminary and by no means as evidence to support any treatment scheme, which is still a topic largely debated with no consensus [21]. Lopinavir and Ritonavir treatment was exclusively used in ICU patients, a case control study published on March 18 th suggested a lack of effect in death reduction [63,64], however ICU attendant from this hospital decided to continue with the antiviral treatment scheme due to the lack of literature consensus and an apparent clinical improvement still on quantification.…”
Section: Discussionmentioning
confidence: 99%
“…Lopinavir/Ritonavir treatment was exclusively used in ICU patients. A case control study published on 18 March 2020, suggested a lack of effect in death reduction [ 61 , 62 ], however the ICU Department from this hospital decided to continue with the antiviral treatment scheme due to the lack of literature consensus and an apparent clinical improvement still on quantification.…”
Section: Discussionmentioning
confidence: 99%
“…At the time of writing, SARS-CoV-2 has infected more than 70 million individuals worldwide and has caused nearly 1.2 million deaths [4]. From viral transmission mechanisms [5] to COVID-19 treatments [6], researchers are attempting to understand the disease dynamics better and reduce its burden on humankind. The global spread of COVID-19 cases drives research to attempt to understand how environmental factors may contribute to SARS-CoV-2 transmission and COVID-19 disease severity [7,8] Along with the spread of the pandemic, most countries imposed a policy of social distancing and other regulations to mitigate COVID-19 [9,10].…”
Section: Introductionmentioning
confidence: 99%